A study on the thermal comfort and clothing insulation characteristics of preschool children in Korea. (October 2015) - Nam, Insick; Yang, Jinho; Lee, Dohee; Park, Eunjung; Sohn, Jong-Ryeul
Abstract: The present study was intended to examine thermal comfort in kindergartens for children aged 4–6 years (preschool children). Centering on Seoul, Korea, thermal comfort characteristics of kindergartens in four seasons (spring, summer, autumn, winter) from June 2013 to May 2014 were evaluated. Indoor/outdoor dry-bulb temperatures, relative humidity, air-flow speed, and globe temperatures. The number of kindergartens included in the study were 19, 29, 21 and 16 during spring, summer, autumn and winter, respectively. The study results were derived through a questionnaire survey on TSV (thermal sensation votes) and metabolism conducted with 994 respondents. The relationships between children's clothing insulation and 4-day weighted mean ambient temperatures, operative temperatures, and outdoor temperatures were evaluated and the results indicated that the amount of clothing was changed the most by operative temperatures. The seasonal mean amounts of clothing were 0.29 clo in summer and 0.81 clo in winter, which were smaller than the amount of clothing of adults presented by ASHRAE. The seasonal amounts of clothing for male and female children differed from each other. In addition, children's comfortable temperatures were identified as being lower than those of adults by approximately 0.5 °C in the summer and by approximately 3.3 °C in the winter, indicating that children have different thermal awareness from adults. Highlights: We have the survey and analysis aimed at 4–6 year olds. We seasonally measured in kindergartens for thermal comfort parameters. Children investigated the lower clothing insulation than adults. Children preferred the lower temperature than adults. Clothing insulation showed a clear change according to operative temperature.